Single-cell scattering and auto-fluorescence-based fast antibiotic susceptibility testing for gram-negative and gram-positive bacteria - Dixneuf, Sophie; Chareire-Kleiberg, Anne-Coline; Mahé, Pierre; El Azami, Meriem; Kolytcheff, Chloé; Bellais, Samuel; Guyard, Cyril; Védrine, Christophe; Mallard, Frédéric; Josso, Quentin; Rol, Fabian (Frontiers in Microbiology, 2023)
In this study, we assess the scattering of light and auto-fluorescence from single bacterial cells to address the challenge of fast (< 2h), label-free phenotypic antimicrobial susceptibility testing (AST). Label-free flow cytometry is used for monitoring both the respiration-related auto-fluorescence in two different fluorescence channels corresponding to FAD and NADH, and the morphological and structural information contained in the light scattered by individual bacteria during incubation with or without antibiotic. Large multi-parameter data are analyzed using dimensionality reduction methods, based either on a combination of 2D binning and Principal Component Analysis, or with a one-class Support Vector Machine approach, with the objective to predict the Susceptible or Resistant phenotype of the strain. For the first time, both Escherichia coli (Gram-negative) and Staphylococcus epidermidis (Gram-positive) isolates were tested with a label-free approach, and, in the presence of two groups of bactericidal antibiotic molecules, aminoglycosides and beta-lactams. Our results support the feasibility of label-free AST in less than 2 hours and suggest that single cell auto-fluorescence adds value to the Susceptible/Resistant phenotyping over single-cell scattering alone, in particular for the mecA+ Staphylococcus (i.e. resistant) strains treated with oxacillin.